2012
DOI: 10.1111/j.1600-0587.2012.06882.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of plant beta‐diversity along elevational and latitudinal gradients in mountain forests of China

Abstract: Biodiversity patterns and their underlying mechanisms have long been focal topics of study for ecologists and biogeographers. However, compared with spatial variation in species richness (a-and g-diversity), b-diversity, or the dissimilarity of species composition between two or more sites has until recently received limited attention. In this study, we explored the large-scale patterns of altitudinal turnover (b-diversity) of plants in montane forests of China, based on systematic inventories of 1153 plots fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
69
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 59 publications
(165 reference statements)
14
69
3
1
Order By: Relevance
“…This pattern may also indicate the indirect impact of altitudinal gradients and topographic aspects on the species composition by limiting the habitat quality and suitability such as soil fertility, precipitation and temperature to support the vegetation which thereby shape the spatial structure of the community assemblages [29][30][31][32][33]11]. Moreover, our study is in congruent with the findings of the previous studies [33][34][35][36] that indicated the effect of altitude gradient on species composition. Here, the species composition may be determined by the ecological processes such as environmental filters, biotic interactions and species specific neutral mechanism properties such as dispersal limitation [20,30,37,38].…”
Section: Discussionsupporting
confidence: 82%
“…This pattern may also indicate the indirect impact of altitudinal gradients and topographic aspects on the species composition by limiting the habitat quality and suitability such as soil fertility, precipitation and temperature to support the vegetation which thereby shape the spatial structure of the community assemblages [29][30][31][32][33]11]. Moreover, our study is in congruent with the findings of the previous studies [33][34][35][36] that indicated the effect of altitude gradient on species composition. Here, the species composition may be determined by the ecological processes such as environmental filters, biotic interactions and species specific neutral mechanism properties such as dispersal limitation [20,30,37,38].…”
Section: Discussionsupporting
confidence: 82%
“…The mountains provide a natural boundary between the north and the south of the country and between the temperate and tropical zones, and support a huge variety of plants and wildlife, making the Qinling Mountains one of the hotspots for species richness in China. Although elevational patterns of diversity for plants and animals are well established in the Qinling Mountains (Tang et al 2012), we know little about how AMF diversity varies across elevational gradients. This is a serious gap in our general understanding of biodiversity, given that AMF are abundant and diverse and play a central role in ecosystem functioning and processes (Smith and Read 2008).…”
Section: Introductionmentioning
confidence: 99%
“…; Tuomisto ,b; Tang et al. ,b). Previous studies have extensively explored mechanisms underlying the spatial turnover of species, among which niche theory and neutral theory have gained most attention.…”
Section: Introductionmentioning
confidence: 99%
“…; Tang et al. ), partly because of the dependence of species interactions and environmental filtering on temperature (Sakai & Weiser ; Huntley et al. ; Randin et al.…”
Section: Introductionmentioning
confidence: 99%